Analisis Deformasi Vertikal Dan Horisontal Tanah Lunak Di Bawahpiled-Geogrid Supported Embankment - Adhe Noor Patria (Jenderal Soedirman University, 2010)
Soft soil was easily founded in Indonesia. it was a low permeability soil. Constructing building such as embankment, roads on this kind of soil often faced problems. They were long term settlement, long term construction time and consolidation. Some method could be good alternative to overcome these problems such the usage of vertical drains, soil reinforcement, orsoil stabilization. This research carried out numerical simulation on piled-geogrid supported embankment. The simulation used Plaxis version 7.2 software to calculate some iterations. Used in this software as soil parameter input was Mohr-Coulomb Soil Model. Plane strain model was used for floating piles and geogrid. The results showed that the usage of floating piles and geogrid could reduce soil deformation. The reduction in horizontal deformation during contructing embankment were 60 to 68 % for rigid embankment and 80 to 60 % for interface embankment. Meanwhile the reduction in vertical deformation during contructing embankment were 60 to 65 % for rigid embankment and 80 to 65 % for interface embankment..